Multitrait factor structure of control tests for power development program in soccer - Yamada, H.; Nishijima, T. (International Journal of Sport & Health Science, 2003)
The purpose of this study was to apply the multitrait factor structure model to the control test used for the power development program for soccer players that is hierarchically constructed and to confirm contributions of the task motor skill to the test performances. Subjects were 103 male college soccer players tested on 15 items selected by qualitative characteristic attribution analysis to construct a hypothetical structure of the control test following the power training phase. Test-retest reliability of the power tests was examined. The feasibility of the multitrait factor structure model was confirmed with the structural equation modeling. It was made apparent how power and skill factors were involved in the test performance. We concluded that multiple power subdomains and multiple motor skill domains are involved in control tests consisting of multiple motor tasks. The power and skill differ in contributions in each test. There is a relationship between motor skills involved in test performance, which becomes the basis of control test arrangement.